Using Quality Improvement Methods to Implement an Electronic Medical Record (EMR) Supported Individualized Home Pain Management Plan for Children with Sickle Cell Disease - Crosby, Lori E. (2014)
OBJECTIVE: Using quality improvement methodology, our goal was to develop and implement individualized home pain management plans (HPMP) that included pharmacologic as well as non-pharmacologic strategies for children with sickle cell disease (SCD). We hypothesized that successfully implemented HPMPs would have an impact on Emergency Department (ED) use, decreasing ED visits for uncomplicated SCD pain episodes. METHODS: A multidisciplinary quality improvement team developed a questionnaire to assess the frequency, location and severity of a patient’s pain during a routine, comprehensive visit in order to help the patient and family develop an effective pain management strategy using both pharmacologic and non-pharmacologic actions. Using plan do study act cycles (PDSAs), this team was able to build this process into the daily workflow for all SCD patients age 5 years to 21 years of age. Patients with comprehensive visits scheduled from January 2012 to May 2013 were included (N=188) in the intervention. RESULTS: By May of 2013, 88% of eligible patients had an individualized HPMP in place. There was a concomitant reduction in the percentage of SCD patients seen in the ED for uncomplicated SCD pain (6.9% vs. 1.1%). CONCLUSIONS: Using quality improvement methods, an individualized HPMP intervention was incorporated successfully into the daily workflow of a busy outpatient SCD clinic. This intervention has the potential to improve patient outcomes by decreasing avoidable ED visits as well as reducing overall healthcare costs.